PROGRAM PENGABDIAN MASYARAKAT MELALUI WORKSHOP ANALISIS DATA PENELITIAN BIDANG PENDIDIKAN MENGGUNAKAN SOFTWARE SPSS - Sofiyanurriyanti Sofiyanurriyanti; Nailul Izzah; Anik Rufaidah; Moh Ririn Rosyidi (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2021)
Education research data analysis workshop using SPSS software is one form of higher education Tridharma that must be implemented by lecturers, namely community service. The purpose of this workshop is to provide insight and knowledge about data processing using statistics assisted by SPSS software, especially among teachers of TK Muslimat NU 29 Mahkota Gresik. This workshop was attended by 21 participants from TK Muslimat NU 29 Mahkota Gresik. The workshop was held for 1 day starting at 08.00 WIB - 16.00 WIB, on 27 January 2019 to be precise. The material provided at this workshop included descriptive statistics, data distribution measures, data centering measures, hypothesis testing and correlation analysis. The feedback from this workshop was to provide training in analyzing data using SPSS software. The final result of this workshop participants were able to analyze data using SPSS software.